IRA's and household saving revisited some new evidence - Attanasio, Orazio P. 1959-; DeLeire, Thomas C. (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1994)
The effectiveness of tax-favored savings accounts in raising national savings depends crucially upon the willingness of households to reduce consumption in order to finance contributions to these accounts. The debate over the tax deductibility of IRA's has centered on whether IRA contributions represented new savings or reshuffled assets. We devise a test to distinguish between these two hypotheses where we compare the behavior of households which just opened an IRA account with that of households which already had an IRA account. Our test accounts for any unobservable heterogeneity across the two groups. We find evidence that supports the view that households financed their IRA contributions primarily through reductions in their stocks of other assets. Our results indicate that less than 20% of IRA contributions represented addition to national savings.